Transforming carbon nanotube forest from darkest absorber to reflective mirror - Saleh, Tanveer; Moghaddam, Mehran Vahdani; Mohamed Ali, Muhamed Sultan; Dahmardeh, Masoud; Foell, Charles Alden; Nojeh, Alireza; Takahata, Kenichi (American Institute of Physics, 2012)
Carbon nanotube (CNT) forests are known to be among the darkest materials on earth. They can absorb the entire visible range of electromagnetic wave more efficiently than any other known black material. We have attempted controlled mechanical processing of the CNTs and, surprisingly, observed mirror-like reflection from the processed area with 10%–15% reflectivity, a level higher than typical reflectivity of pure forests by over two orders of magnitude, for a wide range of the spectrum (570–1100 nm). Patterning of micro mirrors in the forest is demonstrated to show its potential application for producing monolithically integrated reflector-absorber arrays in the material